1998
DOI: 10.1007/s004240050638
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of deoxygenation-induced increase in tyrosine kinase activity in sickle cell dehydration

Abstract: Deoxygenation of sickle (SS) cells causes cationic alterations leading to cell dehydration by various mechanisms, including activation of Ca2+-sensitive K channels and possibly of K-Cl cotransport. Since an abnormal tyrosine kinase (TK) activity exists in SS cells we investigated the possible role of tyrosine phosphorylation in SS cell dehydration. In density-fractionated SS reticulocytes and discocytes, but not in normal red cells, deoxygenation increased membrane and cytosolic TK activities and tyrosine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…1 In a previous study, to characterize the cell signaling events that lead to the dehydration of deoxygenated SS cells, we have shown that deoxygenation increased protein tyrosine kinase (PTK) activity and that PTK inhibitors reduced SS cell dehydration by decreasing the K ϩ loss either in the presence or absence of Ca ϩϩ in the medium without affecting SIP. 2 These data provide evidence that either one or both K ϩ transporters might be regulated by a pathway implicating a tyrosine phosphorylation. Unlike in SS cells, PTK activity in normal red cells (AA cells) was not affected by deoxygenation.…”
Section: Introductionmentioning
confidence: 82%
“…1 In a previous study, to characterize the cell signaling events that lead to the dehydration of deoxygenated SS cells, we have shown that deoxygenation increased protein tyrosine kinase (PTK) activity and that PTK inhibitors reduced SS cell dehydration by decreasing the K ϩ loss either in the presence or absence of Ca ϩϩ in the medium without affecting SIP. 2 These data provide evidence that either one or both K ϩ transporters might be regulated by a pathway implicating a tyrosine phosphorylation. Unlike in SS cells, PTK activity in normal red cells (AA cells) was not affected by deoxygenation.…”
Section: Introductionmentioning
confidence: 82%
“…As reported by us and by others, 10,11,19,[35][36][37][38]40,42 malarial parasite invasion, shrinkage of the erythrocyte in response to hypertonic stress, and exposure of the cell to oxidative stresses such as those that derive from hemoglobin denaturation/hemichrome formation, thalassemias, sickle cell disease, glucose-6-phosphate dehydrogenase, other antioxidant deficiencies, and natural aging all lead to enhanced band 3 tyrosine phosphorylation. 22,23,26 Among these stimuli, oxidative stress appears to be the most proficient, and indeed recent data demonstrate that oxidative cross-linking of band 3 directly induces its association with Syk, which in turn triggers phosphorylation of tyrosines within its cytoplasmic domain. 20 Consistent with these findings, only the oxidized fraction of band 3 becomes phosphorylated after imposition of an oxidant stress.…”
Section: Regulation Of Membrane-cytoskeletal Interaction 6003mentioning
confidence: 99%
“…20,21 In response to physiologic stimuli such as hypertonic conditions or oxidative stress, and in severe hematologic disorders such as thalassemias, sickle cell anemia, and glucose-6-phosphate dehydrogenase deficiency, 22,23 phosphorylation of band 3 on tyrosine residues can increase by several orders of magnitude. 20,[22][23][24][25][26] Although the protein tyrosine kinase Lyn has been shown to participate in this phosphorylation, 21 the protein tyrosine kinase Syk can be argued to play the more prominent role, because it has been reported to phosphorylate tyrosines 8 and 21 of band 3, 20 which in turn generates a binding site for other protein tyrosine kinases. 21 Of more direct relevance to erythrocyte signal transduction, Syk may also mediate the effects of oxidant stress on band 3 tyrosine phosphorylation, because it strongly prefers to phosphorylate a reversibly oxidized conformation of AE1.…”
Section: Introductionmentioning
confidence: 99%
“…In sickle-cell disease, exposing the red cells to deoxygenation resulted in increased tyrosine kinase activity, concommittant with cellular dehydration. 18 Terra et al reported that the steady-state level of band 3 tyrosine phosphorylation is elevated 2-10 fold in various types of sickle cell disorder and approximately 4 fold in β-thalassemia intermedia. 19 However, tyrosine phosphorylation of β-spectrin was not documented.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that oxidative stress affects β-spectrin phosphorylation by modification of spectrin kinases/phosphatases, or by alterating the spatial arrangement of membrane proteins. [18][19][20][21][22] Reduced tyrosine kinase activity of membrane proteins is observed in Scott syndrome, a hereditary bleeding disorder characterized by a deficiency in prothrombinase activity caused by defective phospholipid scrambling activity of the blood cell membrane. 23 The decrease in membrane phospholipid scrambling results in reduction in phosphatidyl serine (PS) exposure and in prothrombinase activity on the cell surface.…”
Section: Discussionmentioning
confidence: 99%